A Comparison of Three Different Agents of Decalcification for a Histological Examination of Bone Tissues - Gul, Mehmet; Bayat, Nuray; Gul, Semir; Huz, Mustafa; Yildiz, Azibe; Otlu, Ali (Annals of Medical Research, 2021)
None